TORCH-R trial protocol: hypofractionated radiotherapy combined with chemotherapy and toripalimab for locally recurrent rectal cancer: a prospective, single-arm, two-cohort, phase II trial - Wan, Juefeng; Wu, Ruiyan; Fu, Miaomiao; Shen, Lijun; Zhang, Hui; Wang, Yan; Wang, Yaqi; Zhou, Shujuan; Chen, Yajie; Xia, Fan; Zhang, Zhen (Frontiers in Oncology, 2023)
For patients with locally recurrent rectal cancer (LRRC), the response rate to chemoradiotherapy is 40-50%. Additionally, only approximately 40-50% of patients with recurrent rectal cancer are able to undergo R0 resection. Recent studies in locally advanced rectal cancer (LARC) have shown promising synergistic effects when combining immunotherapy (PD-1/PD-L1 antibodies) with neoadjuvant chemoradiotherapy (nCRT). Therefore, incorporating immunotherapy into the treatment regimen for LRRC patients has the potential to further improve response rates and prognosis. To investigate this, the TORCH-R trial was conducted. This prospective, single-arm, twocohort, phase II trial focuses on the use of hypofractionated radiotherapy, chemotherapy, and immunotherapy in LRRC patients without or with oligometastases. The trial will include two cohorts: cohort A consists of rectal cancer patients who are treatment-naive for local recurrence, and cohort B includes patients with progressive disease after first-line chemotherapy. Cohort A and cohort B patients will receive 25-35Gy/5Fx irradiation or 15-25Gy/5Fx reirradiation for pelvic recurrence, respectively. Subsequently, they will undergo 18 weeks of chemotherapy, toripalimab, and stereotactic ablative radiotherapy (SABR) for all metastatic lesions between chemoimmunotherapy cycles. Decisions regarding follow-up of complete response (CR), radical surgery, sustained treatment of non-resection, or exiting the trial are made by a multidisciplinary team (MDT). The primary endpoint of this study is the local objective response rate (ORR). The secondary endpoints include the extrapelvic response rate, duration of response, local recurrence R0 resection rate, progression-free survival (PFS), overall survival (OS), as well as safety and tolerability. Notably, this trial represents the first clinical exploration of inducing hypofractionated radiotherapy, chemotherapy, and immunotherapy in LRRC patients.